Gum ghatti-alginate hybrid bead derived titania spheres for deep removal of toxic dye Remazol Brilliant Violet from aqueous solutions - Preeti; Banerjee S.; Debnath A.; Singh V. (My University, 2025)
Mesoporous titania spheres was achieved using titanium (IV) isopropoxide as precursor and alginate-gum ghatti composite beads as structure directing agent via the low-temperature sol-gel synthesis method.These polysaccharides are multi-functional in nature & exhibiting secondary interactions in solution to accept new rheological and textural properties. The mixed beads of adequate mechanical strength could be obtained by keeping the ratio>1:1 for alginate to gum ghatti. The synthesized spheres were extensively characterized using FTIR, BET, SEM, TEM, and XRD. TEM study revealed that hollow titania spheres (HSAG3) are formed through the aggregationof TiO2 nanoparticles. Adsorption activity of titania spheres was investigated by employing Remazol Brilliant Violet (RBV) dye as the model reactive azo dye compounds. The dye adsorption mechanism was investigated indepthly using various kinetics models. Adsorption data found to be well expressed through pseudo second-order kinetics model. Further, data was also interpreted through Boyd model and the obtained diffusion constant value found to be in the order of 10−17 cm2/m, suggesting pore diffusion mechanism plays significant role in governing overall rate of the sorption process. The adsorption equilibrium data better conformed with the Langmuir isotherm which indicates surface homogeneity of the spheres for dye adsorption. Recycling study prompted that the adsorbent can be employed successively for 5 consecutive times without observing any significant loss in adsorption capacity. Overall the study revealed that the titania spheres can be serve as a promising adsorbent specifically for the removal of Remazol Brilliant Violet dye and other reactive anionic azo dyes in general. © 2021